Use of tylvalosin in the control of porcine enzootic pneumonia. Issue 1 (30th June 2015) - Pallarés, F. J.; Lasa, C.; Roozen, M.; Ramis, G.
Abstract : Objectives: The purpose of this study was to investigate the efficacy of tylvalosin (Aivlosin Water Soluble Granules, ECO Animal Health) in drinking water for control of Mycoplasma hyopneumoniae (M hyo) on a farm with chronic enzootic pneumonia (EP) problems and high prevalence of mycoplasma‐like lesions at slaughter. Design: On a 4000‐sow farm in the southeast of Spain, 1500 animals of same age were randomly divided into two groups: 900 pigs in the treated group (TG) and 600 pigs in the non‐treated control group (CG). TG was medicated for seven days with tylvalosin in drinking water (2.5 mg tylvalosin/kg bodyweight (BW)) at weaning (from 21st to 28th day of life) and a second treatment when moved to finisher barn (from 63rd to 70th day of life). Results: In the TG, there was a significant reduction in the severity (P<0.001) and number of animals with lung lesions (P<0.001) compared with CG. TG had an increased average daily gain and decreased average number of days in finishing. TG had a lower average carcase weight, but improved homogeneity. M hyo was not detected by q‐PCR in samples, taken from lungs with characteristic EP lesions in the TG (0/9), in contrast to the CG (8/9 positive). Conclusions: A strategic medication with Aivlosin at 2.5 mg tylvalosin/kg BW in drinking water for seven days at weaning and when moved to finisher barn significantly reduces mycoplasma‐like lung lesions and improves productivity parameters.